2011
DOI: 10.1002/ejoc.201101249
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Vitamin B12 Derivatives: Unprecedented Formation of a 7‐Membered Lactam

Abstract: The synthesis of a new hydrophobic cobalamin derivative through intramolecular aminolysis is described. Under acidic conditions, (CN)2CobIII(10‐NH2)7C1‐ester formed a seven‐membered lactam between the ester and amino groups present at the C8 and C10 positions. Subsequent Boc protection of the NH group enabled ring opening with primary amines, leading to derivatives functionalized at the C8 and C10 positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In our study, we used hydrophobic heptamethylcobyrinate as a model compound. Several selective modifications of such hydrophobic derivatives have already been described, [8] however, to the best of our knowledge, copper catalyzed azide-alkyne cycloaddition has not been explored for this purpose, though it was found to have practical applications in medicinal, bioconjugate, supramolecular chemistry and material science. [9] Moreover, the use of CuAAC for connection of tetrapyrrole compounds is still challenging from the synthetic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we used hydrophobic heptamethylcobyrinate as a model compound. Several selective modifications of such hydrophobic derivatives have already been described, [8] however, to the best of our knowledge, copper catalyzed azide-alkyne cycloaddition has not been explored for this purpose, though it was found to have practical applications in medicinal, bioconjugate, supramolecular chemistry and material science. [9] Moreover, the use of CuAAC for connection of tetrapyrrole compounds is still challenging from the synthetic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the treatment of a hydrophobic vitamin B 12 derivative, heptamethyl dicyanocobyrinate ((CN) 2 Cby(OMe) 7 ), with 65 % nitric acid gives a nitrated derivative of cobalamin in 78 % yield . Unfortunately, applying the same conditions for the nitration of 1 results in a mixture of products and only 19 % yield of the desired (CN)Cbl(10‐NO 2 ) ( 2 ) (Table , entry 1).…”
Section: Resultsmentioning
confidence: 82%
“…Firstly, we focused on derivatives modified at the meso ‐position because it is known that such modifications, through the cis effect, influence the nature of the central cobalt atom . The presence of meso ‐Br− ( 10 ), −Cl ( 11 ) or −NH 2 ( 13 ) substituents in the catalyst structure had little to no effect on the model reaction yield, but fluctuation in the ratio of products ( 5 / 6 ) was observed (Table , entries 2, 3 and 5).…”
Section: Resultsmentioning
confidence: 99%